KEPUTUSAN KONSUMEN UNTUK MENABUNG PADA BANK RAKYAT INDONESIA SYARIAH CABANG MAKASSAR - Kasnaeny K Jibril (Lembaga Penelitian dan Publikasi Nobel Indonesia, 2009)
This Research mean to analyze about behavior and factors which background of consumer decision to save at Bank of BRI Moslem law. This Research use 60 responder and variable becoming research [is] factors becoming fascination a bank of Moslem law as much 12 variable. This variable is tested with the method Analyse the Factor. From result analyse the factor, all variable summarized to become 3 of nucleus;core factor. Pursuant to examination result to 12 variable, obtained by 2 nucleus;core factor that is : (1) factor of product and service which Islami, as biggest first factor of its influence, and ( 2) Personal factor as second factor